Упростите выражения: a) m-(n+m) b) - (n-x) - x
в) a-(a-b)
g) g+(x-g)
d) p+(-m+r-p)
e) - a-(m-a+p)
ё) m+(r-a-m)
ж) - (m-a) - (r+a)
з) m-(a+m) - (-a-m) ​

Alenadobro97 Alenadobro97    2   28.12.2020 15:32    0

Ответы
barbariskaulyaЮлия barbariskaulyaЮлия  27.01.2021 15:36

Вроде бы так

Пошаговое объяснение:

1) m-n+x-x =m-x

2) - n+x-x= - n

3) a-a+b=b

4)g+x-g=x

5) p-m+r-p= - m+r

6) - a-m+a-p= - m-p

7) m+r-a-m = r-a

8)-m+a-r-5

9) m-a-m+a+m = m

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика